Using Tyler's Theory Of Curriculum Modelling For Effective Development Of Arabic In The Contemporary Nigerian Tertiary Institutions - Yusuf Abdul Azeez; Kazeem Oluwatoyin Ajape (ELK Asia Pacific Journals, 2024)
This study attempts to trace the foundation of the teaching and learning of Arabic language as a course of study in the Nigerian tertiary institutions in an effort to revive the curriculum of Arabic language in the light of contemporary challenges for nation building and human development. Hence the study explore the perspectives of students in the Arabic Departments in one of the universities in the South West, Nigeria in order to find indepth solutions to their observations regarding the present state of the programme in the Nigerian tertiary institutions. The process of getting an accurate data for this research was guided by Tyler’s theory of curriculum modelling. Efforts were, therefore, made in this paper to identify the grassroots’ problems and misconception of the Nigerian Society about the language of Arabic itself, Tyler’s theories of curriculum modeling were put into test in order to proffer solution to the fear raised by the students of Arabic Language in Nigeria, and the contemporary effort and approach of the Federal government of Nigeria to enhance the learning of the language in Nigeria were also emphasised. Going by the prevailing circumstances identified in this study, it establishes the fact that the present curriculum is not in conformity with the philosophy and goals of the national policy on education. The study, therefore, proposes a new dimension for the teaching and learning of Arabic language by stressing the need to teach the language for other career purposes apart from the religious one. The study, thus, comes up with suggestions that may be useful for designing a purposeful curriculum of Arabic language for the tertiary institutions in Nigeria.